Operating and Activity Competence of the Education Manager - Iryna Myshchyshyn; Khrystyna Kalahurka; Orest Myshchyshyn (Pedagogical Discourse, 2020)
The attention is paid to the modern processes of the updating of a social-cultural mission of education, which cause a change of the educational paradigm and as a result of the contents and ways of the activity of modern educational institutions. It is determined that an activity competence of a manager is essential on all the levels of leader’s work: planning, conducting, motivating, control, estimating of work of all the objects of the administrative process. It includes special technological skills of the organisation of a managerial process, taking decisions, putting right team’s work, environment of upholders, providing conditions for the dividing of duties and delegacy of authority, conducting of a systematic and opportune control on all the levels, consolidation of a democratic style of guidance, achieving of collective leadership and participation. The peculiarities of the realization of the operating and activity competence and practical skills are clarified in the process of applying different managerial techniques: guidance via delegacy, exceptions, aim, results, conflicts, control and direction, motivation, innovations, communication, invigilation.On the basis of systematization and generalization of the material mentioned above, the essential role of operating and activity component in the system of professional competence of a manager of education is stated. Practical skills of a leader are formed in the process of a professional preparing and are improved under the conditions of active and creative professional activity. The diversity of the tasks and functions of the professional activity of a manager is caused by modern demands and it is reflected in the appearance of new forms of the operating and activity competence, improvement of discrete skills and systematic complexes, modes of a leader’s mastery. The determination of a spectrum of the operating and activity competence is essential for the organization of a qualitative preparing of the future experts-leaders in the educational sphere.